2023
DOI: 10.1038/s41598-023-28156-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and HIV detection by blood RNA-sequencing in cohort of smokers

Abstract: Detection of viruses by RNA and DNA sequencing has improved the understanding of the human virome. We sought to identify blood viral signatures through secondary use of RNA-sequencing (RNA-seq) data in a large study cohort. The ability to reveal undiagnosed infections with public health implications among study subjects with available sequencing data could enable epidemiologic surveys and may lead to diagnosis and therapeutic interventions, leveraging existing research data in a clinical context. We detected v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although 30/31 participants (97%) in the HCV Follow-Up Study either reported a previous or received a new HCV diagnosis, the false-positive and false-negative rates for the research HCV RNA-seq results for predicting clinically confirmed HCV are uncertain since the HCV status of participants who did not participate in the HCV Follow-Up Study was not systematically ascertained. We did not perform clinical HCV testing on previously collected COPDGene samples for several reasons: 1) The study consent form did not specify that HCV clinical testing would be performed; 2) We believed that the available evidence from our previously published article on viral sequence detection suggested that the HCV RNA-seq results were likely at least reasonably accurate 14 ; and 3) Since the samples were not handled with a CLIA chain of custody, clinical testing would be required to confirm the results. However, the high percentage of participants who spontaneously volunteered a previous HCV diagnosis at the initial phone call suggests that the research HCV RNA-seq test is likely at least reasonably accurate for clinical HCV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 30/31 participants (97%) in the HCV Follow-Up Study either reported a previous or received a new HCV diagnosis, the false-positive and false-negative rates for the research HCV RNA-seq results for predicting clinically confirmed HCV are uncertain since the HCV status of participants who did not participate in the HCV Follow-Up Study was not systematically ascertained. We did not perform clinical HCV testing on previously collected COPDGene samples for several reasons: 1) The study consent form did not specify that HCV clinical testing would be performed; 2) We believed that the available evidence from our previously published article on viral sequence detection suggested that the HCV RNA-seq results were likely at least reasonably accurate 14 ; and 3) Since the samples were not handled with a CLIA chain of custody, clinical testing would be required to confirm the results. However, the high percentage of participants who spontaneously volunteered a previous HCV diagnosis at the initial phone call suggests that the research HCV RNA-seq test is likely at least reasonably accurate for clinical HCV.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reported 14 , 228 COPDGene participants with suggestive evidence of HCV (defined as “HCV results”) were identified by applying PathSeq 26 to blood RNA-seq reads that were not mapped to the human genome. As shown in Table 1 , we developed a procedure for returning HCV results, which separated the clinically important notification about potential HCV infection from a follow-up research study regarding the downstream effects of the return of results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral blood is the tissue of choice in clinical diagnostics and biomedical research due to minimally invasive sample collection. As blood perfuses all organs, it provides insights into various diseases and medical conditions 1,2 . In general, we can investigate active pathways and organismal responses to stimuli (e.g., a viral infection) on a transcriptomic level 3,4 by using well-established sequencing techniques such as bulk RNA sequencing (RNA-seq).…”
Section: Introductionmentioning
confidence: 99%